2008
DOI: 10.1093/aje/kwn137
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Screening Approach for Assessing Community Prevalence and Phenotype of Polycystic Ovary Syndrome in a Semiurban Population in Sri Lanka

Abstract: In most of South Asia, prevalences and phenotypes of polycystic ovary syndrome (PCOS) among women in the community are unknown. The authors aimed to estimate prevalence and phenotype in a community setting in Sri Lanka and to test a valid, feasible screening approach to early diagnosis. A community-based, cross-sectional study was carried out in 2005-2006. A random sample of 3,030 women aged 15-39 years was selected by cluster sampling proportionate to population size. An interviewer-administered questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
108
2
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(124 citation statements)
references
References 15 publications
6
108
2
4
Order By: Relevance
“…However, the approximation of ultrasound features for women declining the transvaginal ultrasound examination may be biased, as it can be assumed the majority of symptomatic women are more concerned about their health and, therefore, more inclined to be investigated. Furthermore, a recent community-based study from Sri Lanka [150] reports 6.3% of women of childbearing age have PCOS, according to the 2003 Rotterdam criteria Hirsutism was not assessed by physicians nor was an ultrasonographic examination of the ovaries performed in this prevalence study: this could be considered a weakness of the study. Besides the inter-rater variability in hirsutism scorings, the feasibility of the Ferriman-Gallwey score is impaired as many women treat the symptoms prior to clinical evaluation; thus, it is unlikely an objective assessment of hirsutism would have yielded a more accurate measure of clinical hyperandrogenism.…”
Section: Paper Imentioning
confidence: 89%
See 1 more Smart Citation
“…However, the approximation of ultrasound features for women declining the transvaginal ultrasound examination may be biased, as it can be assumed the majority of symptomatic women are more concerned about their health and, therefore, more inclined to be investigated. Furthermore, a recent community-based study from Sri Lanka [150] reports 6.3% of women of childbearing age have PCOS, according to the 2003 Rotterdam criteria Hirsutism was not assessed by physicians nor was an ultrasonographic examination of the ovaries performed in this prevalence study: this could be considered a weakness of the study. Besides the inter-rater variability in hirsutism scorings, the feasibility of the Ferriman-Gallwey score is impaired as many women treat the symptoms prior to clinical evaluation; thus, it is unlikely an objective assessment of hirsutism would have yielded a more accurate measure of clinical hyperandrogenism.…”
Section: Paper Imentioning
confidence: 89%
“…Besides the inter-rater variability in hirsutism scorings, the feasibility of the Ferriman-Gallwey score is impaired as many women treat the symptoms prior to clinical evaluation; thus, it is unlikely an objective assessment of hirsutism would have yielded a more accurate measure of clinical hyperandrogenism. Furthermore, a simple symptom-based questionnaire may be useful for identifying women with an endocrine profile typical for PCOS [33,150]. In Sri Lanka, more than 90% of women with self-reported symptoms of oligo/amenorrhea and/or hirsutism were later shown to have PCOS [150].…”
Section: Paper Imentioning
confidence: 99%
“…The community prevalence of PCOS ranges between 2% to 11% in various countries with ethnic diversity in its age specific prevalence (Wijeyaratne et al, 2013) and the community prevalence of PCOS in young premarital Sri Lankan women is 6.3 % ( Kumarapeli et al, 2008). It is reported that 40-80% of PCOS women are overweight or obese (Barber et al, 2006, Wher et al, 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Recruitment of Subjects: Women whose symptoms manifested from adolescent years (11)(12)(13)(14)(15)(16)(17)(18)(19) years WHO), with all 3 diagnostic criteria present when aged between 16-19 years (Anovular PCOS, hyperandrogenism and polycystic ovaries on ultrasound) were recruited as cases. Women who are asymptomatic, non-androgenic, normal cycling, in whom PCOS was objectively excluded by clinical, biochemical and ultrasound assessment, were recruited as controls.…”
Section: Methodsmentioning
confidence: 99%
“…A study conducted among a semiurban population in Sri Lanka has demonstrated that the prevalence of PCOS is 6.3% (2).…”
Section: Introductionmentioning
confidence: 99%